Mariano Ponce and the Philippine–American War: A View of the Man and His Deeds Through His Letters from Japan - Zialcita, Jean Paul (Social Science Diliman: A Philippine Journal of Society and Change; Vol 7 No 2 (2011))
The article takes a closer look at the character and deeds of Mariano Ponce, a key actor in the Philippine struggle for independence from Spain and, later, the United States.  This is done through a detailed examination of several letters he wrote in 1899 while stationed in Japan as representative of the Philippine revolutionary government headed by General Emilio Aguinaldo. The letters allow a deepened understanding and appreciation of Ponce as revolutionary and patriot and enhance our grasp of a pivotal event in the Philippine’s past: the Philippine-American War of 1899–1902.
Keywords: Mariano Ponce, Cartas sobre la Revolución, Philippine-American war, Philippine history